(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2024)
The aim of the article is to present theoretical applications of project management models. This analysis aims to demonstrate possible ways of project management. The article emphasizes the continuous evolution of techniques, methods, and methodologies in project management, highlighting new concepts such as CSR, Agile, Scrum, and Kanban. The author set out to examine the characteristics of team project management, assuming the hypothesis that knowledge about available resources conditions effective management. The verification of this hypothesis included a literature review and a case analysis using SWOT analysis.